(3GdJShjb GdOhdj h GdGdcJQhfjs - (3fjajf MSjf(B, (3TeJs ((3GdGScfOQjI(B:s (3OGQ GdJYdje GdLGeYj(B,s, 2010)
(3JYQja GdJShjb h CgejJg h eQGMd JWhQ GdacQ GdJShjbj, GdJShjb GdOhdj h GSJQGJjLjI GdJQhjL, GdJShjb GdGdcJQhfj h GdJLGQI GdGdcJQhfjI, OhQ fXGe GdeYdheGJ GdJShjbjI h HMhK GdJShjb aj JNWjW GdfTGW , Jbjje h JMdjd GdHjFI GdOGNdjI GdefXeI cCSGS dJMOjO fbGW GdbhI h GdVYa, JbSje GdShb Gdi bWGYGJ cCSGS dJMOjO GdCShGb GdeSJgOaI, GdJfHD HGdWdH Ydi GdSdY h GdNOeGJ h CNjQG HMhK GdJShjbs
Keywords: (3GdJLGQI GdNGQLjIs; (3GdJShjb GdEdcJQhfjs; (3GdJShjb GdOhdjs